Kant and Hegel in Dickens' Selected Works - Taghi Beigi, Parivash (2011)
Human beings from time immemorial have experienced the desire to know or understand themselves, other people, and their environment. I propose to clarify these desires by bringing together the theories of two famous philosophers: Immanuel Kant (in the 18th century) and George Wilhelm Friedrich Hegel (in the early 19th century). When Kant’s transcendental idealism and his view of good-will together with Hegel’s dialectic argumentation and his view of free-will is brought alongside three of Charles Dickens’ novels, I expect to introduce a new reading of Dickens. The novels in question are Oliver Twist, David Copperfield and Great Expectations. Not only the theories of Kant and Hegel but also Dickens’ use of first-person narrators (Oliver, David and Pip) should enable us to understand the stark environment of his time. For that reason, my research contemplates the effects of a close analysis of Kantian transcendental idealism, good-will as well as Hegel’s concepts and thoughts of dialect, free-will, and the sequence of hope on Dickens’ selected literary works. Furthermore, it aims to understand how Dickens adopts his novels’ plots to echo these philosophies. It is a skill that needs new means to re-read Dickens. In this respect, the study starts to re-read Dickens skillfully and wisely, while employing ethical methodology approaches to cover both the significance of Dickens’ selected novels as well as concluding how the above-mentioned thoughts and concepts are common to the characters’ narrative voice, particularly in Dickens’ Oliver Twist, David Copperfield and Great Expectations. As a result, the research seeks out the truth that defines how the reality of Dickens’ novels is related to the relevant time and place of his period, and how the novels are Dickens’ transcended world to Oliver, David and Pip, and from Oliver, David and Pip to the reader. As a result, the research shows that the variety existing in the arrangement of his characters stems from the existed variety in his own experiences. Yet, to estimate the extent of this variety, a close examination or analysis of the arrangement of the characters is needed. An argumentation over the arrangement of two groups of characters, good-will and bad-will characters shows the fundamental process of progression and development in thought, reality and morality of Dickens’ characters.Indeed the result of this analysis creates a comprehensive vision, and illuminates the influence of Kantian transcendental idealism, good-will as well as Hegel’s concepts and thoughts of dialect, free-will and the sequence of hope in Dickens’ selected literary works.